1994
DOI: 10.1128/aac.38.2.184
|View full text |Cite
|
Sign up to set email alerts
|

Use of multivariate analysis to compare antimicrobial agents on the basis of in vitro activity data

Abstract: PCA and factor analysis assist in the identification of the interrelationships of multiple variables, all acting simultaneously. Multivariate methods handle large volumes of data resulting from the interactions of multiple variables and identify principal components or factors that link some of the variables and that unlink others. There are as many components or factors identified as there are variables studied. The information provided by the factors is not identical; the first factors reflect links of a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…One previous study applied principal component analysis and factor analysis to identify groups of antibiotics with similar trends in MIC from 15 groups of microbes from 17 studies. 17 Rotated principal components correspond to dense subregions in PGMs. 15 The PGMs give a more detailed picture of how the variables are correlated in a way that is visually interpretable and more detailed and that requires fewer assumptions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One previous study applied principal component analysis and factor analysis to identify groups of antibiotics with similar trends in MIC from 15 groups of microbes from 17 studies. 17 Rotated principal components correspond to dense subregions in PGMs. 15 The PGMs give a more detailed picture of how the variables are correlated in a way that is visually interpretable and more detailed and that requires fewer assumptions.…”
Section: Discussionmentioning
confidence: 99%
“…The MIC values were log 2 transformed so that a unit change corresponded to a single 2-fold dilution. 14 , 17 …”
Section: Methodsmentioning
confidence: 99%
“…There have been a few previous studies that have approached AMR as a multivariate problem, but they have not applied a chain graph or comparable approach. One previous study applied principal component analysis and factor analysis to identify groups of antibiotics with similar trends in MIC from 15 groups of microbes from 17 studies (Hernandez and Conforti 1994). Rotated principal components correspond to dense subregions in probabilistic graphical models, i .…”
Section: Discussionmentioning
confidence: 99%
“…HO (n = 1927) and HACO (n = 5201) isolates were both classified as healthcare-acquired. The minimum inhibitory concentration (MIC) values were log 2 transformed so that a one unit change in the transformed value would correspond to a change of one two-fold dilution as used in microbroth dilution plates (Love et al 2016; Hernandez and Conforti 1994). Susceptibility results which exceeded the highest tested concentration were increased by one dilution, e.g., MIC > 16 ug/mL was re-coded MIC = 32 ug/mL with log 2 (MIC) = 5.…”
Section: Methodsmentioning
confidence: 99%
“…The ability of multivariate methods to portray the impact of antibiotic usage on resistance patterns has been suggested before [12,13]. Applying multivariate techniques, those investigators found a high degree of correlation between the activities of OXA, CLI/ERY and CTR against isolates of S aureus and postulated that this species underwent similar evolutionary resistance pressures for these antibiotics.…”
Section: Principal Component Analysis Of the Data Proved To Bementioning
confidence: 99%